Sistem Informasi Monitoring Proses Pembelajaran di STMIK STIKOM Indonesia - Pratama, I Putu Adi; Ariana, Anak Agung Gede Bagus (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
The Lecture Program Unit (SAP) consists of determining learning objectives, the material to be discussed, how to present it, supporting media and learning resources that can be used. At the end of each teaching and learning activity, for the purposes of monitoring and evaluation, teaching staff are required to write SAP realization in a teaching journal. At STMIK STIKOM Indonesia, the process of writing this teaching journal is done manually. The lecturer filled out the material given in class in a teaching journal. The process is done manually resulting in the process of monitoring and evaluation can not be done regularly. In this research, a Web-based monitoring system for teaching and learning process was developed in STMIK STIKOM Indonesia. From the test results obtained, the system built can facilitate lecturer coordinator lecturers to monitor the course of the teaching and learning process. In addition, the system built can also facilitate lecturer coordinator lecturers in conducting the recapitulation process of the suitability of SAP with the realization of SAP written by lecturers supporting courses